2017
DOI: 10.3390/ijms18030674
|View full text |Cite
|
Sign up to set email alerts
|

ROS Production and ERK Activity Are Involved in the Effects of d-β-Hydroxybutyrate and Metformin in a Glucose Deficient Condition

Abstract: Hypoglycemia, a complication of insulin or sulfonylurea therapy in diabetic patients, leads to brain damage. Furthermore, glucose replenishment following hypoglycemic coma induces neuronal cell death. In this study, we investigated the molecular mechanism underlying glucose deficiency-induced cytotoxicity and the protective effect of d-β-hydroxybutyrate (D-BHB) using SH-SY5Y cells. The cytotoxic mechanism of metformin under glucose deficiency was also examined. Cell viability under 1 mM glucose (glucose defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…ROS can initiate apoptosis of podocytes, induce podocytes to exfoliate from basement membrane, and decrease the number of podocytes in glomeruli . Metformin can not only inhibit the production of NADPH oxidase and AGEs, thus reducing ROS content in podocytes cultured in vitro, but also reduce oxidative stress by increasing the activity of peroxidase and the production of SOD and GSH . In this study, the BG, serum uric acid, BUN and UACR decreased significantly in MET ( P < .01) treatment group compared with that of DM group, and the decreased levels were metformin‐dependent.…”
Section: Discussionmentioning
confidence: 48%
“…ROS can initiate apoptosis of podocytes, induce podocytes to exfoliate from basement membrane, and decrease the number of podocytes in glomeruli . Metformin can not only inhibit the production of NADPH oxidase and AGEs, thus reducing ROS content in podocytes cultured in vitro, but also reduce oxidative stress by increasing the activity of peroxidase and the production of SOD and GSH . In this study, the BG, serum uric acid, BUN and UACR decreased significantly in MET ( P < .01) treatment group compared with that of DM group, and the decreased levels were metformin‐dependent.…”
Section: Discussionmentioning
confidence: 48%
“… 10 , 11 The primary molecular role of Met is inhibiting mitochondrial respiratory complex I, namely, reduced nicotinamide adenine dinucleotide (NADH) dehydrogenase, which could reduce cellular synthesis of ATP and induce reactive oxygen species (ROS) imbalance. 12 In fact, some studies have indicated that Met could increase the level of ROS in lung cancer and breast cancer, 13 , 14 but no report has shown the association of biguanides and ROS in glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…In case of ERK, it was reported that MPP + increased α-synuclein expression through ROS production and the increased α-synuclein expression inactivated ERK, thereby increasing caspase 3 activation [ 71 ]. We previously reported that glucose deficiency increased ROS production and decreased ERK phosphorylation in SH-SY5Y cells [ 72 ]. Interestingly, ROS inhibitor clearly recovered ERK phosphorylation decreased by glucose deficiency, suggesting ROS-induced downregulation in ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%